SIFO 1986: Environment and employment - the two most important issues - Swedish Institute of Public Opinion Research; Federation of Swedish Industries (Swedish Institute of Public Opinion Research, 1993)
This survey was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the Federation of Swedish Industries. The respondent was asked about the three most important political issues and about the two most important causes of environmental pollution in Sweden. Opinion on increasing, decreasing or unchanged industrial emissions during the past three years. Confidence in the way Swedish industry handles environmental issues and whom the respondent trust most in environmental issues. Other questions dealt with use of electricity: possibilities of economic growth without increasing the use of electricity, future supply of electricity, and what to concentrate on for increasing the supply of electricity. Background variables include information on gender, age, Swedish citizenship, occupation, private or public sector, right to vote in general elections, voting habit, political party preference and party voted for in 1985.

This survey was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the Federation of Swedish Industries. The respondent was asked about the three most important political issues and about the two most important causes of environmental pollution in Sweden. Opinion on increasing, decreasing or unchanged industrial emissions during the past three years. Confidence in the way Swedish industry handles environmental issues and whom the respondent trust most in environmental issues. Other questions dealt with use of electricity: possibilities of economic growth without increasing the use of electricity, future supply of electricity, and what to concentrate on for increasing the supply of electricity. Background variables include information on gender, age, Swedish citizenship, occupation, private or public sector, right to vote in general elections, voting habit, political party preference and party voted for in 1985.
SIFO 1986: Miljön och sysselsättningen - de två viktigaste frågorna
Keywords: Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Social Sciences; Samhällsvetenskap